Pendampingan Pengembangan Digitalisasi Bank Soal HSK 1-2 dan CP/ATP Kurikulum Merdeka dengan Implementasi Asesmen Digital - Aiga Ventivani; Jovanni Rizqi Azzahra; Salsabila Isny Ramadhani; Rayyan Anggoro Masdiyanto; Nouval Aurum Fitransyah (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
This community service program aimed to enhance the capacity of the Mandarin Language Teachers' Association (MGMP) of Malang City in developing a digital HSK 1–2 question bank integrated with Learning Outcomes (CP), Learning Objectives Flow (ATP), and digital assessment implementation. The program was carried out through needs analysis, development of a Google Workspace-based platform, training, mentoring in item development, implementation, and evaluation. The results showed the establishment of a centralized digital question bank repository using Google Drive, Google Sheets, and Google Forms, complete with metadata, a validation system, and integration of CP and ATP. In addition, teachers successfully developed more than 200 HSK 1–2 equivalent test items, independently managed digital assessments, and strengthened collaboration in developing and utilizing assessment instruments. In conclusion, the program successfully improved teachers' competencies in digital assessment development while producing a standardized and sustainable digital question bank to support the implementation of the Merdeka Curriculum.